2016
DOI: 10.3389/fnins.2016.00021
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid Regulation of Food-Choice Behavior in Humans: Evidence from Cushing's Syndrome

Abstract: The mechanisms by which glucocorticoids regulate food intake and resulting body mass in humans are not well-understood. One potential mechanism could involve modulation of reward processing, but human stress models examining effects of glucocorticoids on behavior contain important confounds. Here, we studied individuals with Cushing's syndrome, a rare endocrine disorder characterized by chronic excess endogenous glucocorticoids. Twenty-three patients with Cushing's syndrome (13 with active disease; 10 with dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…Cortisol Levels. Twenty-four hour Urinary Free Cortisol (UFC) and serum cortisol levels were quantified by gas chromatography-mass spectroscopy as described 12 . The limit of sensitivity of this assay is 2ng with inter-assay coefficients of variations <10%.…”
Section: Blood Parametersmentioning
confidence: 99%
“…Cortisol Levels. Twenty-four hour Urinary Free Cortisol (UFC) and serum cortisol levels were quantified by gas chromatography-mass spectroscopy as described 12 . The limit of sensitivity of this assay is 2ng with inter-assay coefficients of variations <10%.…”
Section: Blood Parametersmentioning
confidence: 99%
“…Glucocorticoids (GCs) are known to mobilize the endocannabinoid system which is essential for negative feedback regulation of the hypothalamic–pituitary–adrenal axis [ 63 ]. In addition, a recent study using Cushing’s syndrome patients as a unique model of chronic GCs exposure demonstrated a negative correlation of urine cortisone with food-related choice thus implying a potential role of GR in food-choice behavior [ 64 ]. STAT family members and PDX1 TF were found to be overrepresented from SNP-surrounding sequences from both Prudent and Western reported dietary pattern-associated SNPs ( Tables S5 and S6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, 60% of obese women with PCOS were categorized with binge eating behaviors, and multivariate regression revealed factors including total food cravings, emotional eating scores, and BMI as significant predictors of binge-eating symptom scores in PCOS patients (Jeanes et al ., 2017 ). Whereas in Cushing's Syndrome, abnormal glucocorticoid levels might be driving changed food-reward responses (Moeller et al ., 2016 ). The research compared the appetite symptoms of type 2 diabetes mellitus (T2DM) patients with non-diabetic controls.…”
Section: Perspectivementioning
confidence: 99%
“…In conclusion, food cravings, distinct from appetite, are shaped by individual preferences and are intricately tied to one's psychological state. A holistic exploration of this subject, incorporating factors such as ghrelin, leptin, and various neuro-endocrine mechanisms, is paramount (Krishnan et al ., 2016 ) (Parker et al ., 2021 ) (Moeller et al ., 2016 ). As we venture further, incorporating both the biological and behavioral intricacies of this phenomenon into interventions will be vital.…”
Section: Future Directionmentioning
confidence: 99%